Gender in Asian Movie: Narrative Deconstruction Analysis of Rashomon - Rina Sari Kusuma (Department of Communications, Universitas Islam Indonesia, 2017)
Movie, as a means of mass communication, narrating life in a set of binary - that have different privilege. This research wants to examine movie entitled Rashomon, directed by Akira Kurosawa in 1950, in narrating gender as one of characters code that gave diverse contradictive testimonies about the same events; rape and murder. Rashomon used multiple narrators that build the same story from different point of view that lead to the subjectivity and relativity of truth which the director didn’t give the audience clue how to interpret it. The characters that consist of one women and six men give us a glimpse of sign that there is no gender neutrality will be found in this movie, just like what feminist narratologist saying. With deconstructive approach, this research wants to traces the micro-power of textual process, exposing centralizing and unravelling aspects, making less visible aspects more apparent about gender in movie. Deconstructive reading of Rashomon will generating new discourse about binary opposition men/women by questioning masculinity. Keywords: Movie, Gender, Narrative, Deconstruction, Rashomon